KEMAMPUAN CORPORATE GOVERNANCE MEMODERASI PENGARUH MANAJEMEN LABA PADA PAJAK PENGHASILAN - Wini, Ni Wayan Septia; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2014)
Information asymmetry between managers and the government, causing the manager tends to do earnings management for influence magnitude of income tax. The application of the corporate governance as a control and monitoring system in companies is expected to minimize the influence of earnings management to income tax. This study was purposed to examine the influence of earnings management on income tax and ability of corporate governance to moderate the influence of earnings management on income tax. The data samples of this study are taken from the annual report of 35 manufacturing companies listed in Indonesia Stock Exchange in 2010-2012. Data was collected by observation non participant method. Earnings management was computed by Jones Modified Model and corporate governance represented by four dimension. The multi regression method was implemented in this study. This study results show that earnings management had significant positive influence to income tax and corporate governance had significant negative influence to moderate the influence of earnings management on income tax.
Keywords: corporate governance, earnings management, earnings tax